Public Relations Innovation in Socializing Government Programs through E-Government in West Nusa Tenggara - Elvira Salsabila; M. Ulfatul Akbar Jafar; Irfandi Pratama; Setiawan Ardi Wijaya (Civic Governance and Public Administration, 2025)
Government Public Relations as a public service institution (public sector) is not spared from the need and demands to master and apply technology in carrying out all its duties and activities, but in implementation there are several obstacles both internally and externally such as difficulties in switching from conventional to digital, lack of human resources, and difficulties in collaborating with the private sector The purpose of the research on how to innovate in the public sector carried out by Public Relations Command Center in the context of socializing the work program of the West Nusa Tenggara Provincial Government. public sector innovation carried out by the Public Relations Command Center in the socialization of the work program of the West Nusa Tenggara Provincial Government, namely Service Innovation, Service Process Innovation and Service Method Innovation This research uses qualitative research focus to direct researchers in finding relevant results. So to identify innovations, it is necessary to know the forms or forms of innovation itself in the socialization of government work programs at the public relations bureau of West Nusa Tenggara province by utilizing journals, articles and books. The target group of this Public Relations Command Center innovation is Regional Leaders, Vertical Agencies, Heads of OPDs in West Nusa Tenggara Province, Regency/City Governments, Village Governments and all elements of West Nusa Tenggara society, the inhibiting factor in implementation is that there are no clear rules at the level of regional regulations, thus causing a lack of clarity in the status and career path of the Public Relations Command Center expert team This can cause bottlenecks in the process of developing innovations Related Public Relations Command Center due to teamwork motivation that is disrupted by career clarity status.